Demonstrasi Plot Pemeliharaan Ayam Ras Petelur Sebagai Rintisan Terbentuknya Kampung Unggas di Desa Rempek Kabupaten Lombok Utara - Mohammad Hasil Tamzil; Budi Indarsih; Pardi Pardi; Oscar Yanuarianto (Universitas Mataram, 2019)
The program of demonstration plot in Rempek Village, North Lombok Regency was expected to become a pioneer for laying chicken farm in the regency. Prior to development of planned facilities, site survey was conducted to find the purposed location and focus discussion group. The demonstration plot used house system with 6 x 20 m in width and length extending from east to west. The cage was built using mild construction iron poles and roofed using spandex. The roof was in a monitor-shape with half–open walls on the north and south sides. 550 cages were put iniside the house to keep 1100 pullets. For the pullet row put next to the walls, they were placed with the heads facing inwards; meanwhile for the pullets in the middle rows, they were placed back to back with each other. Every cage was equipped with a feeder and a nipple. During the rearing process, the pullets were fed 110 g/head/day of a mixture of commercial concentrate, corn, and bran with the ratio of 2:4:4, while drinking water was given ad libitum. The production process was normal with egg production peak reaching 92%. After 4 weeks of the peak production, North Lombok Regency was hit by several earthquake, causing the decrease of egg production for the feed was too procey for the production to continue